The Influence of Student Management on the Formation of Student Character at SMA PGRI Rumpin Bogor. - Agus Tamami; Syifa Fauziah (al-Afkar, Journal For Islamic Studies, 2024)
This research is motivated because seeing the problem of character values owned by students in Indonesia is still quite low, schools are one of the environments that affect the formation of student character. So that this study was conducted with the aim of determining the influence of student management in the formation of student character at PGRI Rumpin High School Bogor. The research method used is quantitative method. The population of this study was 248 students and the sample used was 153 students in class X and XI using simple random sampling techniques, and data collection using questionnaires. The research data were then analyzed using the t-test. The result of this study is that there is a significant influence between student management and student character building. This is evidenced by the acquisition of the value of the magnitude of thitung = 6.054 > ttabel = 1.654 with a signification rate of 0.000 < 0.05, then H0 is rejected and Ha is accepted or it can be said that variable X (Student Management) affects variable Y (Student Character Building). The influence of student management on the formation of student character at SMA PGRI Rumpin was 19.5% and the rest was influenced by other variables that were not studied and discussed in this study.